Profil Pertanyaan Inkuiri Guru pada Pembelajaran IPA di Sekolah Dasar - Anggraeni, Poppy; Sopandi, Wahyu; Widodo, Ari (Mimbar Sekolah Dasar, 2018)
This study aims to describe the profile of teachers’ inquiry questions of science lessons in the 5th grade of Elementary School on the topic of Water. The method used in this research was a descriptive method and the sample was 16 elementary schools in Sumedang city. The results showed that the profile of inquiry question in the lesson plan document is distributive very low, the question that arises is the questions that require students to make a hypothesis only (5.56%). In the science-learning process, there are four categories of inquiry questions that appear very low in distribution (2.63%). In daily evaluation, the distribution of questions is very low, the questions only require students to hypothesize (6.73%). Based on the above analysis, it can be concluded that the emergence of the teacher inquiry question profile is still uneven and very low. Therefore it is suggested that there is an integrated training program on inquiry learning which includes the preparation of lesson planning, learning activities and science learning evaluation.